Центральний державний архів-музей літератури і мистецтва України: історія, джерельна база, сьогоднішні реалії - Ходоровський, М. (Архіви України, 2008)
The article reflects the history of establishing the Central State Archives and Museum of Literature and Art of Ukraine, its main foundations and the structure of the source base. Special emphasis is made on CSAMLAU activities in terms of popularization of the archival documents as well as the top-priority issues to be immediately solved.